Home Business Creativity, New Model Innovation for New Normal Era MSMEs in Ngagel Rejo Village, Surabaya City - Siti Samsiyah; Catur Ade Alfian (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2021)
This study aims to analyze the influence of New Model Innovation Creativity, Home Business, and MSMEs in the New Normal Era in Ngagel Rejo Village, Surabaya City. The population in this study amounted to 380 MSMEs and the research sample amounted to 77 respondents while the formula technique used slovin. For data collection using questionnaires and documentation then analyzed using Multiple Linear Regression Test, t-test and F-test. The results of the analysis carried out using the t-test concluded that the variables of New Model Innovation Creativity and Home Business have a partial and significant effect on SMEs in the new normal era. With the results of the New Model Innovation variable, the t-count is 2,977 with a sig value of 0.004, while the F test results are 457.848 with a sig value of 0.000. Home Business Creativity t-count is 10,366 with sig 0.000.